Preeclampsia: knowledge from health professionals about risk factors, complications and preventive strategies (Research, Society and Development, 2025)
Objective: to analyze the knowledge of Family Health Strategy professionals about risk factors, complications and strategies that can be developed to prevent pre-eclampsia in maternal-fetal health. Methodology: This is a qualitative study, which involved the participation of nine professionals, including doctors and nurses. Data collection was carried out through semi-structured interviews, organized using Bardin's content analysis technique. Results: Regarding risk factors, the professionals' knowledge includes genetic factors, obesity, diabetes, and a previous history of preeclampsia, with complications that affect the mother and the fetus. Regarding prevention measures, they emphasize the importance of prenatal care as early as possible, with health education and drug prophylaxis with ASS and calcium. However, this knowledge was not presented in a systematized manner and supported by guidelines or theoretical references. Conclusion: With this, reflecting on the magnitude and complexity that permeates this problem is to realize that health professionals alone will not be able to guarantee this quality and comprehensiveness so desired in health care, calling pregnant women, municipal health management and the Health Care Network to take responsibility, as well as thinking about actions of Permanent Education in health.